Telltale signs of metal recycling in the circumgalactic medium of a z ∼ 0.77 galaxy. Issue 1 (5th August 2021) - Tejos, N; López, S; Ledoux, C; Fernández-Figueroa, A; Rivas, N; Sharon, K; Johnston, E J; Florian, M K; D'Ago, G; Katsianis, A; Barrientos, F; Berg, T; et al.
ABSTRACT: We present gravitational-arc tomography of the cool-warm enriched circumgalactic medium (CGM) of an isolated galaxy ('G1') at z ≈ 0.77. Combining VLT/MUSE adaptive-optics and Magellan/MagE echelle spectroscopy, we obtain partially resolved kinematics of Mg ii in absorption and [O ii ] in emission. The unique arc configuration allows us to probe 42 spatially independent arc positions transverse to G1, plus four positions in front of it. The transverse positions cover G1's minor and major axes at impact parameters of ≈10–30 and ≈60 kpc, respectively. We observe a direct kinematic connection between the cool-warm enriched CGM (traced by Mg ii ) and the interstellar medium (traced by [O ii ]). This provides strong evidence for the existence of an extended disc that co-rotates with the galaxy out to tens of kiloparsecs. The Mg ii velocity dispersion ( σ  ≈ 30–100 km s −1, depending on position) is of the same order as the modelled galaxy rotational velocity ( v rot  ≈ 80 km s −1 ), providing evidence for the presence of a turbulent and pressure-supported CGM component. We regard the absorption to be modulated by a galactic-scale outflow, as it offers a natural scenario for the observed line-of-sight dispersion and asymmetric profiles observed against both the arcs and the galaxy. An extended enriched co-rotating disc together with the signatures of a galactic outflow, are telltale signs of metal recycling in the z ∼ 1 CGM.